Proposta para Ensino de Matemática com o uso do simulador interativo PhET colorado - Velasco, Moacir (2024)
The objective of this work is to present an alternative approach for primary school teachers who work with teaching mathematics, using the Colorado PhET simulator. The aim is to provide teachers with knowledge about the simulator, along with suggestions on how some concepts normally worked on in elementary and secondary education can be approached through the use of the simulator. The proposals include teaching the initial concepts of fractions, affine functions, quadratic functions and trigonometric functions using PhET. To optimize the presentation of content by teachers, didactic sequences were developed for each topic, in addition to the production of videos to assist in demonstrating the simulator’s resources